Embryotoxic and teratogenic effect of Ruta chalepensis L. «rue», in mouse (Mus musculus) - Gonzales, José (2006)
Ruta graveolens L. and R. chalepensis L. are plants used in folkloric medicine as antispasmodics, antihelmintics, antimicrobials, emmenagoges and abortifacients. In this work we evaluated embryotoxic effect of liophilized aqueous extract (LAE) of leaves of R. chalepensis on postimplantational mouse embryos. Pregnant albino mice received intraperitoneally (ip) 10 mg of liophilzed rue/kg of body weight (treated group, n=12) during post implantational period (day 9 - day 17 postcopula), and a control (C) group, n=18, received only distilled water during the same period of time. The LAE of R. chalepensis did not affect negatively the weight of mother but affected the weight of the uterus during the period of treatment (p<0,05). The frequency of fetal resorptions was greater (p<0,05) and a significant decrease of fetal weight (p<0,01) was evidenced in fetuses of the treated group in comparison with the C group. Also there was occurrence of skeletal malformations in the treated group. In conclusion, we found that LAE of R. chalepensis shows embryotoxic effects on mouse esposed during postimplantational period.